Overestimation of maximal aerobic speed by the Université de Montréal track test and a 1500-m-time trial in soccer - Thron, Maximiliane; Woll, Alexander; Klos, Leon; Härtel, Sascha; Ruf, Ludwig; Kloss, Christian; Altmann, Stefan (Frontiers in Physiology, 2022)
Introduction. Maximal aerobic speed (MAS), usually measured by cardiopulmonary exercise testing (CPET) on a treadmill, is gaining popularity in soccer to determine aerobic performance. Several field tests are used to estimate MAS, although, gold standard methods are still not clarified. Therefore, this work aims i) to compare two different CPET based methods to assess MAS and ii) to investigate the convergent validity of two common field tests to estimate MAS in soccer. Methods. Thirteen trained male soccer players completed an CPET on a treadmill to determine two VO2-kinetic based definitions of MAS (MASPlateau=speed at onset of VO2-plateau=gold standard; MAS30s=first speed of 30-s-interval of VO2max), the Université de Montreal Track Test (UMTT; VUMTT=speed of the last stage), and a 1500-m-time trial (1500-m-TT; V1500m=average speed). MASPlateau, MAS30s, VUMTT, and V1500m were compared using ANOVA. Additionally, limits of agreement analysis (LoA), Pearson's r, and ICC were calculated between tests. Results. MAS30s, VUMTT, and V1500m significantly overestimated MASPlateau by 0.99 km/h (ES=1.61; p<0.01), 1.61 km/h (ES=2.03; p<0.01) and 1.68 km/h (ES=1.77; p<0.01), respectively, with large LoA (-0.21≤LoA≤3.55), however with large-to-very large correlations (0.65≤r≤0.87; p≤0.02; 0.51≤ICC≤ 0.85; p≤0.03). Discussion. The overestimation and large LoA of MASPlateau by all estimates indicate that i) a uniform definition of MAS is needed and ii) the UMTT and a 1500-m-TT seem questionable for estimating MAS for trained soccer players on an individual basis, while regression equations might be suitable on a team level. The results of the present work contribute to the clarification of acquisition of MAS in soccer.